Drug-Drug Interactions at Organic Cation Transporter 1 - Zhou, Shiwei; Zeng, Sujuan; Shu, Yan (Frontiers in Pharmacology, 2021)
The interaction between drugs and various transporters is one of the decisive factors in the pharmacokinetics and pharmacodynamics of drugs. The organic cation transporter 1 (OCT1) is a member of the solute carrier 22A (SLC22A) family that plays a vital role in the membrane transport of organic cations including endogenous substances and xenobiotics. This article mainly discusses the drug-drug interactions (DDIs) mediated by OCT1 and their clinical significance.